EFEKTIVITAS PENGGUNAAN MODEL ROUND TABLE DALAM MENINGKATKAN HASIL BELAJAR PPKN SISWA KELAS X - Ahmad Fadhilah Suandi; Rum Rosyid; Ika Rahmatika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aims to determine the effectiveness of using a round-table learning model to improve learning outcomes of 10th-grade Social Science 1 students in SMAN 2 Nanga Pinoh. This research used an experimental method in the form of pre-experimental research with "One Group Pretest-posttest" design. The population in this study was the 10th-grade students of SMAN 2 Nanga Pinoh, of which 25 from class X Social Science 1 were taked as the sample. The research instruments for data collection used were interview sheets, observation sheets, tests items for pretest and posttest, and validity and reliability test sheets. Base on the data analysis, the pretest and posttest scores are respectively 57,60 and 77,00. The effect size by 2,7 ≥ 0,8 which is category as high indicates that the use of a round-table learning model is effective to use in improving learning outcomes in Civic Education Subjects for students of class X Social Sciences 1 SMAN 2 Nanga Pinoh.Keywords: (Effectiveness, Round Table Learning Model, Civic Education)